Myosin VI maintains the actin-dependent organization of the tubulobulbar complexes required for endocytosis during mouse spermiogenesis. Issue 4 (4th January 2020) - Zakrzewski, Przemysław; Suwińska, Anna; Lenartowski, Robert; Rędowicz, Maria Jolanta; Buss, Folma; Lenartowska, Marta
Abstract: Myosin VI (MYO6) is an actin-based motor that has been implicated in a wide range of cellular processes, including endocytosis and the regulation of actin dynamics. MYO6 is crucial for actin/membrane remodeling during the final step of Drosophila spermatogenesis, and MYO6-deficient males are sterile. This protein also localizes to actin-rich structures involved in mouse spermiogenesis. Although loss of MYO6 in Snell's waltzer knock-out (KO) mice causes several defects and shows reduced male fertility, no studies have been published to address the role of MYO6 in sperm development in mouse. Here we demonstrate that MYO6 and some of its binding partners are present at highly specialized actin-based structures, the apical tubulobulbar complexes (TBCs), which mediate endocytosis of the intercellular junctions at the Sertoli cell-spermatid interface, an essential process for sperm release. Using electron and light microscopy and biochemical approaches, we show that MYO6, GIPC1 and TOM1/L2 form a complex in testis and localize predominantly to an early endocytic APPL1-positive compartment of the TBCs that is distinct from EEA1-positive early endosomes. These proteins also associate with the TBC actin-free bulbular region. Finally, our studies using testis from Snell's waltzer males show that loss of MYO6 causes disruption of the actin cytoskeleton and disorganization of the TBCs and leads to defects in the distribution of the MYO6-positive early APPL1-endosomes. Taken together, we report here for the first time that lack of MYO6 in mouse testis reduces male fertility and disrupts spatial organization of the TBC-related endocytic compartment during the late phase of spermiogenesis. Abstract : Myosin VI, a unique motor protein, is involved in the late phase of spermatid development by maintaining spatial integrity of testis-specific actin-rich structures—the apical tubulobulbar complexes. Graphical Abstract: